Identification of Colonial Architectural Elements on Building Facades in Bengkulu City - Abdul Hamid Hakim; Mohammad Nur Dita Nugroho; Siti Munawarah Panggabean; Dwi Utami; Ringga Salsabila (Jurnal Lingkungan Binaan Indonesia, 2026)
The British and Dutch colonial invasion in Bengkulu left the image of the colonial area in the Khadijah and KH Ahmad Dahlan roads. Eight colonial buildings were found to be warehouses, residences, and schools, in a state of disrepair, neglect, or damage, so feared they would be erased. The research aims to identify colonial architectural elements on façades using a qualitative approach, collecting data from observations, documentation, interviews, and the literature to classify façades or conduct visual interpretation based on colonial architectural theory. The results revealed that the visual characteristics of the façade comprised 2 types of roofs, 2 types of walls, 3 types of floors, 2 types of doors, and 2 types of windows.  Elements of colonial architecture, namely the gable, bouvenlicht, nook actroterie, and geveltoppen with a terrace, as in Berendo, in the traditional house of Bengkulu. Bengkulu's colonial buildings are interpreted as symbols of superiority, cultural acculturation, and adaptation to the tropical climate. The results can enrich architectural science and serve as a reference for the preservation of colonial architecture in the city of Bengkulu.